Long term nexus between digitalization and macroeconomy on zakat collection in Indonesia - Suprayitno, Aryadimas; Hawariyuni, Weni; Pratomo, Wahyu Ario; Hasibuan, Widya Sartika; Andrasari, Monika; Widiastuti, Tika; Susanto, Arva Athallah (Review of Islamic Social Finance and Entrepreneurship, 2025)
Purpose – This study aims to investigate the long-term and short-term impacts of digitalization and macroeconomic factors on zakat collections in Indonesia. It explores and validates the successful use of the Internet and a country's economic conditions to maximize zakat collection.Methodology – This study employs annual time series data from 1991 to 2024 to examine zakat collections in Indonesia, with digitalization and macroeconomic performance as the key exogenous variables. The selected period captures major economic disruptions, including the Asian Financial Crisis, 2008 global financial crisis, and post-pandemic recovery. The Autoregressive Distributed Lag (ARDL) model was applied to assess the long-short dynamic relationship effect among the variables.Findings – This study addresses hypothesis by empirically confirms that the integration of digitalization and macroeconomic improvements plays a pivotal role in enhancing zakat collections in Indonesia. The findings reveal a favorable long-term and short-term impact of digitalization on zakat collection, and long-term positive effects and short-term negative effects of macroeconomic conditions.Implications – This study provides critical insights for BAZNAS and other zakat institutions in designing and implementing sustainable digital strategy policies that enhance zakat mobilization and management efficiency. By integrating digital transformation initiatives with a forward-looking approach to future economic dynamics, zakat organizations can strengthen transparency and improve donor engagement.Originality – This research presents a unique contribution by addressing the scarcity of studies on zakat collections that incorporate both long-term and short-term analyses. Furthermore, research incorporating macroeconomics and digitalization as external factors in the study of zakat remains limited.